Effect of CT screening on smoking habits at 1-year follow-up in the Danish Lung Cancer Screening Trial (DLCST). Issue 5 (3rd December 2008) - Ashraf, H; Tønnesen, P; Holst Pedersen, J; Dirksen, A; Thorsen, H; Døssing, M
Abstract : Background: The effect of low-dose CT screening for lung cancer on smoking habits has not been reported in large randomised controlled trials. Methods: This study evaluated the effect on smoking habits of screening with low-dose CT at 1-year follow up in the Danish Lung Cancer Screening Trial (DLCST), a 5-year randomised controlled trial comprising 4104 subjects; 2052 subjects received annual low-dose CT scan (CT group) and 2052 received no intervention (control group). Participants were healthy current and former smokers (>4 weeks since smoking cessation) with a tobacco consumption of >20 pack years. Smoking habits were determined at baseline and at annual screening. Smoking status was verified using exhaled carbon monoxide levels. Lung function tests, nicotine dependency and motivation to quit smoking were assessed. Quit rates and relapse rates were determined at 1-year follow-up for all subjects. Results: At 1 year the quit rates among smokers were 11.9% in the CT group and 11.8% in the control group (p = 0.95). Relapse rates for former smokers were 10.0% and 10.5% in the CT and control groups, respectively (p = 0.81). Significant predictors (p<0.05) for smoking cessation were: high motivation to quit, low dependency, low ratio of forced expiratory volume in 1 s to forced vital capacity, low pack years, higher age, longer period of abstinence and CT findings necessitating 3-month repeat CT scans. Conclusions: Overall, quit rates were similar in the CT and control group at 1-year follow-up, with a net quit rate of 6.0%. Quit rates were higher and relapse rate lower among subjects with initial CT findings that necessitated a repeat scan 3 months later.